An Obsolescing Bargain in a Rentier State: Multinationals, Artisanal Miners, and Cobalt in the Democratic Republic of Congo - Zeuner, Brett (Frontiers in Energy Research, 2018)
Drawing from theories on the political-economy of natural resources, this paper broadens the discussion surrounding cobalt sourced from the former Katanga region of the Democratic Republic of Congo; specifically, the use of that cobalt in rechargeable lithium-ion batteries as energy storage in electrified transportation and distributed energy systems. Two theories, Rentier State and Obsolescing Bargaining, are applied to the cases of multinational and artisanal cobalt mining operations in the former Katanga region. Risks between the DRC government and multinational cobalt mining companies are compared to the risks present in artisanal cobalt mining. Additionally, this paper explores how the decision to include or exclude Congolese, artisanal cobalt from supply chains involves broader questions of bargaining power, political stability, and resource dependency. Additionally, this paper expands consideration to explore how the inclusion of artisanal cobalt in the supply chain might impact political stability and corruption in the DRC, rather than focusing on how Western or Chinese purchasers of electrified vehicles, for example, might perceive the suitability of the product’s supply chain. By relating artisanal cobalt mining to multinational mining companies and the broader political issues present in the DRC, decision-makers can better consider current and historical outcomes as part of a broader political-economy that includes both artisanal and multinational mining. Furthermore, this paper hopes to provide a robust argument for the transparent and intentional inclusion of artisanal cobalt in electrified vehicle supply chains to make the transition to low-carbon transportation more sustainable through improvements to measures of social sustainability in the DRC.